Freight Traffic Analytics from National Truck GPS Data in Thailand - Nattaphon Chankaew; Agachai Sumalee; Siripirote Treerapot; Thanunchai Threepak; H.W. Ho; William H.K. Lam (My University, 2018)
Recently, demand of freight transport increases tremendously and cause serious impacts on traffic congestion and air quality. In 2015, The Department of Land Transport of Thailand has introduced a project named "Nationwide Confidence with GPS Onboard" to install GPS tracking system on all trucks in Thailand. This project provides new sources of data in analyzing the freight-related traffics and designing remedial measures for freight-related issues. This paper aims to demonstrate the use of GPS data in determining truck activities, estimating truck origin-destination matrix and estimating the flow of different commodities. Thailand is used as a case study to demonstrate the results.
Keywords: Transportation Planning and Optimization